Information technologies in the economy (Eurasian Scientific Herald, 2023)
This article is devoted to the main components of information systems and technologies used in various sectors and directions of the national economy. The main focus is on the classification of information and communication technologies, technical tools and their development trends, software and various operating systems, text and tabular information processing, presentation preparation technology, network data processing, the concept of algorithms, using programming languages. focused on the development of programs, information systems and their components, the concept of information systems in management, statistics, tax, accounting, banking, personnel management, information protection in economic systems. This study guide is intended for students of the higher education institution studying "Information and communication technologies and systems", and it can be useful for those who independently study modern information technologies and systems in various fields of the economy